2012
DOI: 10.4149/neo_2012_065
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) expression and mutations in the EGFR signaling pathway in correlation with anti-EGFR therapy in head and neck squamous cell carcinomas

Abstract: Our data suggest that KRAS mutation (p.Gly12Val) and somatic EGFR mutation located in exon 19 may contribute to the limited clinical response to therapy with cetuximab + radiotherapy. Higher EGFR gene expression serves as an independent indicator of good clinical response to EGFR-targeted therapy + radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
(48 reference statements)
3
24
0
Order By: Relevance
“…By contrast, when EGFR expression was assessed by IHC and real time PCR, a prognostic value for high EGFR expression has been associated with reduced PFS and complete response in cetuximab+RT-treated HNSCC patients, in two studies [73, 74]. …”
Section: Egfr Protein Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, when EGFR expression was assessed by IHC and real time PCR, a prognostic value for high EGFR expression has been associated with reduced PFS and complete response in cetuximab+RT-treated HNSCC patients, in two studies [73, 74]. …”
Section: Egfr Protein Expressionmentioning
confidence: 99%
“…In another study, a deletion in exon 19 of EGFR was disclosed in two out of 29 HNSCC patients treated with cetuximab and RT. These two patients presented poor clinical outcome, suggesting that this mutation may contribute to the limited response [74]. …”
Section: Egfr Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] This mutation is most prevalent in malignant gliomas (20-30% in unselected patients with a glioblastoma multiforme [GBM] and 50-60% in patients whose tumors show amplification of wild-type EGFR). 27 Recent studies identified EGFRvIII in head and neck squamous cell carcinomas (~21%), 28 squamous cell carcinomas of the lung (~5%), 29,30 and breast (~5%), 31 suggesting broader implications to human cancer. 32 EGFRvIII is known to contribute to radio resistance of tumor cells 33 at least in part through enhanced repair of DNA doublestrand breaks.…”
Section: Egfrviiimentioning
confidence: 99%
“…Mutational activation of KRAS only occurred in 2.6 % of 115 clinical specimens of SCCHN, although copy number amplification of KRAS was found in 10 samples (8.7 %) in the same study [229]. In another study, KRAS mutations were found in 4 out of 29 patients with SCCHN and the presence of the G12V KRAS mutation was associated with an absence of response to cetuximab and radiotherapy [230].…”
Section: Kras Mutationmentioning
confidence: 96%